Автор:
katieserranoАвтор:
rusty19Ответ:
38,5
Объяснение:
9а²+6ab+b²-a²+b²=8a²+6ab+2b²=2(4a²+3ab+b²)
2*(4²+3*2*1/2+(1/2)²)=2*(16+3+1/4)=2*19 1/4=2*77/4=77/2=38 1/2=38,5
Автор:
fideltp3c(3a+b)^2-(a+b)(a-b)=
=9a^2+6ab+b^2-(a^2-b^2)=
=9a^2+6ab+b^2-a^2+b^2=
=8a^2+6ab+2b^2=
при а=2 и b=0.5
=8*2^2+6*2*0.5+2*0.5^2=
=8*4+6+2*0.25=
=32+6+0.5=
=38.5
Автор:
bernardq60fДобавить свой ответ
Предмет:
Русский языкАвтор:
kosmo9fptОтветов:
Смотреть
Предмет:
ХимияАвтор:
annabelwallsОтветов:
Смотреть
Предмет:
ИнформатикаАвтор:
deangelo23Ответов:
Смотреть